FORMULASI SEDIAAN ROLL ON AROMATERAPI KOMBINASI MINYAK ATSIRI KRANGEAN (Litsea cubeba (Lour.) Pers.) DAN MINYAK ATSIRI LAVENDER (Lavandula angustifolia Miller) - Chandra, Pra Panca Bayu; Efrilia, Mega; Handayani, Indri Astuti (Jurnal Insan Farmasi Indonesia, 2024)
Krangean and Lavender are natural ingredients producing essential oils. The use of krangean and lavender in the community as perfume ingredients. Krangean essential oil and lavender essential oil contain 1.8 cineol which has potential as aromatherapy. The purpose of the formulation of the Roll on aromatherapy preparation is to determine whether variations in the combination of krangean essential oil and lavender essential oil can affect the test parameters ((organoleptic test, homogeneity test, pH test and favorability test or hedon